Inferences of body energy reserves on conception rate of suckled Zebu beef cows subjected to timed artificial insemination followed by natural mating - Ayres, H.; Ferreira, R. M.; Torres-Junior, J. R. S.; Demetrio, C. G. B.; Sa Filho, M. F.; Gimenes, L. U. [UNESP]; Penteado, L.; D'Occhio, M. J.; Baruselli, P. S. (Elsevier B.V., 2014)
The influence of body condition score (BCS), rump fat thickness (RFAT), and live weight (LW), and the changes in these parameters during the interval from 165 of prepartum (i.e., 125 days of prior gestation) to 112 postpartum on first service conception and pregnancy rates were investigated in suckled Zebu (Bos indicus) beef cows (n = 266) subjected to timed artificial insemination (TAI) followed by natural mating. The aforementioned parameters were recorded at 165 +/- 14 days (mean +/- standard error) prepartum (concurrent with the weaning of previous calf), at parturition, and at 42 +/- 7 days (at the onset of the synchronization of ovulation protocol), 82 +/- 7 days (30 days after TAI), and 112 +/- 7 days (60 days after TAI) postpartum. At the start of the breeding season (BS), cows were subjected to a synchronization of ovulation program for TAI. Bulls were placed with cows 10 days after TAI and remained until the end of the study (112 days postpartum). Cows with the highest BCS at parturition had an increased probability of first service conception rate at 60 days after TAI (P = 0.02) and a reduced probability of occurrence of pregnancy loss (P = 0.05). Also, cows had a greater likelihood of conceiving postpartum if they had greater RFAT and BCS at 165 +/- 14 days prepartum (P = 0.01 and P = 0.03, respectively) and at parturition (P = 0.0007 and P = 0.003, respectively). Cows that had an increase in RFAT and BCS during the dry period (i.e., interval from weaning of the previous calf to parturition) also had a greater likelihood of conceiving (P = 0.03 and P = 0.06, respectively) during the BS. Among the different time points, RFAT and BCS at parturition had the largest impact on risk of conception during the BS. The LW was a poor predictor of conception during the BS (P = 0.11-0.68) except for LW at 165 +/- 14 days prepartum (P = 0.01). Collectively, the findings indicated that the likelihood of conception during the BS was highest in cows that had an improvement in RFAT and BCS during the dry period. Therefore, assuring a good nutritional status in the dry period (BCS >= 3.0 at 165 +/- 14 days prepartum and >= 3.25 at parturition) is an important aim to optimize the postpartum conception rate of suckled Zebu beef cows subjected to TAI followed by natural mating. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Bovine; Bos indicus; Timed artificial insemination; Postpartum conception rate